PELATIHAN YOGA ASANAS DAN PENDALAMAN AJARAN AGAMA HINDU DI SMKN 2 KINTAMANI DESA SONGAN KECAMATAN KINTAMANI KAB. BANGLI - Komang Agus Triadi Kiswara; I Nengah Artawan; Made Novia Indriani; I Gusti Ketut Widana; I Gede Widya Suksma; Kadek Wulan Puspita Dewi; I Gede Badra Buana Putra (JURNAL SEWAKA BHAKTI, 2023)
Lakes are a source of life for the community. As we all know, there are various important functions of lakes in human life, such as irrigating rice fields, fishing, agriculture, and also as a tourist attraction. Likewise, Lake Batur, located in Kintamani District, Bangli Regency, is the largest lake on the island of Bali. Currently, the development of the new lake area focuses on developing the tourism sector, even though on the other hand the lake still needs to be developed in the areas of religion, culture, and tradition, especially for the people who support Lake Batur (Wingkang Ranu). The results of observations made, one form of religious activity that needs to be improved is yoga training as a medium for character education and deepening Hindu religious teachings for school children. The locus for this service activity is SMKN 2 Kintamani which is located in Songan Village, Kintamani District, Bangli Regency. This activity was carried out for two days using the lecture, demonstration, discussion, training, and evaluation methods.